Association Between Gut Microbiota and Helicobacter pylori-Related Gastric Lesions in a High-Risk Population of Gastric Cancer - Gao, Juan-Juan; Zhang, Yang; Gerhard, Markus; Mejias-Luque, Raquel; Zhang, Lian; Vieth, Michael; Ma, Jun-Ling; Bajbouj, Monther; Suchanek, Stepan; Liu, Wei-Dong; Ulm, Kurt; Quante, Michael; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Eradication of Helicobacter pylori has been found to be effective for gastric cancer prevention, but uncertainties remain about the possible adverse consequences such as the potential microbial dysbiosis. In our study, we investigated the association between gut microbiota and H. pylori-related gastric lesions in 47 subjects by deep sequencing of microbial 16S ribosomal RNA (rRNA) gene in fecal samples. The dominant phyla in fecal samples were Bacteroidetes, Firmicutes and Proteobacteria with average relative abundances of 54.77%, 31.37% and 12.91%, respectively. Microbial diversity analysis showed that observed species and Shannon index were increased in subjects with past or current H. pylori infection compared with negative subjects. As for the differential bacteria, the average relative abundance of Bacteroidetes was found to significantly decrease from H. pylori negative (66.16%) to past infection group (33.01%, p=0.007), as well as from normal (76.49%) to gastritis (56.04%) and metaplasia subjects (46.83%, p=0.027). For Firmicutes and Proteobacteria, the average relative abundances showed elevated trends in the past H. pylori infection group (47.11%, 20.53%) compared to negative group (23.44%, 9.05%, p=0.068 and 0.246, respectively), and similar increased trends were also found from normal (18.23%, 5.05%) to gastritis (35.31%, 7.23%, p=0.016 and 0.294, respectively) or metaplasia subjects (32.33%, 20.07%, both p<0.05). These findings suggest that the alterations of fecal microbiota, especially the dominant phyla of Bacteroidetes, Firmicutes and Proteobacteria, may be involved in the process of H. pylori-related gastric lesion progression and provide hints for future evaluation of microbial changes after H. pylori eradication.